2022
DOI: 10.3389/fphys.2021.791036
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Melatonin for Renal Ischemia-Reperfusion Injury: A Systematic Review and Meta-Analysis

Abstract: Background: Renal ischemia-reperfusion (I/R) injury is one of the major causes related to acute kidney damage. Melatonin has been shown as a powerful antioxidant, with many animal experiments have been designed to evaluate the therapeutic effect of it to renal I/R injury.Objectives: This systematic review aimed to assess the therapeutic effect of melatonin for renal I/R injury in animal models.Methods and Results: The PubMed, Web of Science, Embase, and Science Direct were searched for animal experiments apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(199 reference statements)
0
8
0
Order By: Relevance
“…Melatonin shows a protective effect against renal ischemia reperfusion injury, cisplatin-induced nephrotoxicity, reteral obstruction induced renal injury, and radiation injury to kidneys. First of all, melatonin improves renal function and has antioxidative effects on renal ischemia reperfusion injury (16)(17)(18). Moreover, melatonin improves the recovery of renal function through reducing endoplasmic reticulum stress and stimulating the Akt pathway after renal ischemia reperfusion injury (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin shows a protective effect against renal ischemia reperfusion injury, cisplatin-induced nephrotoxicity, reteral obstruction induced renal injury, and radiation injury to kidneys. First of all, melatonin improves renal function and has antioxidative effects on renal ischemia reperfusion injury (16)(17)(18). Moreover, melatonin improves the recovery of renal function through reducing endoplasmic reticulum stress and stimulating the Akt pathway after renal ischemia reperfusion injury (45).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, numerous animal experimental studies about the therapeutic effect of melatonin on renal ischemia reperfusion injury have been published (15)(16)(17)(18). Surprisingly, in animal experiments, melatonin used in combination with chemotherapeutic agents reduces nephrotoxicity (19).…”
Section: Introductionmentioning
confidence: 99%
“…There are several examinations that suggest a potential therapeutic effect of melatonin in minimizing renal injury during ischemia and reperfusion [ 197 , 198 , 199 ]. A histopathological assessment of kidney injury after melatonin treatment showed that the damage was smaller [ 197 ].…”
Section: The Role Of Melatonin In Kidney Diseasesmentioning
confidence: 99%
“…The following information was extracted: the first author's last name, year of publication, animal strain, gender, migraine modeling methodology, number of animals in intervention or control groups, acupuncture manipulation methods (acupoints, electrical stimulator parameters, depth, sessions and retention time), the underlying mechanism of acupuncture, outcome measures, data of mean outcome and standard deviation. If only a chart was used to display the results, the data was gathered by using the software GetData Graph Digitizer 22,23 to accurately measure the values. We attempted to contact the authors to collect the detailed data if the meta-analysis data was missing.…”
Section: Data Extractionmentioning
confidence: 99%